Sindrom Obstruksi Pasca-Tuberkulosis (SOPT): Laporan Kasus - Darmawan, Made Alit; Artawan, I Komang; Rini, Ni Made (PT Kalbe Farma Tbk., 2025)
Pulmonary tuberculosis can cause post-tuberculosis obstruction syndrome as its complication. This case shows symptoms of obstruction in the form of shortness of breath for a month accompanied by cough and weight loss. Patient had a history of pulmonary TB and completely treated pulmonary tuberculosis; the radiology revealed a pathognomonic sign for post-tuberculosis obstruction syndrome such as fibrous infiltrate at the upper lobes of right and left lungs and retracted hilus.